Black Orpheus [videorecording (DVD)] - Camus, Marcel, 1912-1982; Gordine, Sacha; Mello, Breno; Dawn, Marpessa; Oliveira, Lourdes de; Garcia, Léa, 1933-; Moraes, Vinícius de (Criterion collection, 2010)
"Against a background of the Rio carnival, a black tram driver accidentally kills his girlfriend, and after seeking her in the nether regions kills himself to be with her."--Halliwell's Film and video guide, 5th ed.